Hubungan Keterampilan Bertanya Siswa dengan Hasil Belajar Siswa Pada Mata Pelajaran Tematik - Veronica, Rohaya Hida; Nurlaili, Nurlaili; Zubaidah, Zubaidah (PPSDP Undergraduate Journal of Educational Sciences, 2024)
The purpose of this study was to determine the relationship between students’ questioning skills and learning outcomes in thematic subjects in grade 4 of SDN 82 Bengkulu City. This type of research is a quantitative correlational study with a quantitative descriptive approach. The research sample of grade IVB students of SDN 82 Bengkulu City was 26 people with a nonprobability sampling technique using purposive sampling. Data collection techniques were observation, questionnaires, interviews, and documentation. Data analysis used quantitative with the Pearson Correlation Product Moment hypothesis test. The results showed that 11 students’ questioning skills or almost all (42.3%) were in the very good category, 14 people or most (53.8) were in the good category, and 1 person or a small part (3.8%) were in the fairly good category. There is a relationship between students’ questioning skills and learning outcomes of grade IVB students of SDN 82 Bengkulu City with a calculated r value of 0.830> rtable 0.3882 and a significant value of 0.000 <0.05. The results of the product moment correlation analysis show that there is a positive and significant influence between students’ questioning skills and the learning outcomes of class IVB students at SD Negeri 82 Bengkulu City with very strong strength (0.80-1,000).